2018
DOI: 10.1038/nrgastro.2018.5
|View full text |Cite
|
Sign up to set email alerts
|

Acid and the basis for cellular plasticity and reprogramming in gastric repair and cancer

Abstract: Subjected to countless daily injuries, the stomach still functions as a remarkably efficient digestive organ and microbial filter. In this Review, we follow the lead of the earliest gastroenterologists who were fascinated by the antiseptic and digestive powers of gastric secretions. We propose that it is easiest to understand how the stomach responds to injury by stressing the central role of the most important gastric secretion, acid. The stomach follows two basic patterns of adaptation. The superficial respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(108 citation statements)
references
References 248 publications
4
104
0
Order By: Relevance
“…We have termed this the "cyclical hit" model of tumorigenesis (Mills & Sansom, 2015;Saenz & Mills, 2018). Chronic injury of the type that repetitively induces paligenotic/metaplastic events has long been known to increase risk for acquisition of mutations and progression to neoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have termed this the "cyclical hit" model of tumorigenesis (Mills & Sansom, 2015;Saenz & Mills, 2018). Chronic injury of the type that repetitively induces paligenotic/metaplastic events has long been known to increase risk for acquisition of mutations and progression to neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, a critical mutation may be unmasked during paligenosis, and a clone of cells that is unable to redifferentiate arises. We have termed this the "cyclical hit" model of tumorigenesis (Mills & Sansom, 2015;Saenz & Mills, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The atrophy and metaplasia stage is the first in the gastric cancer progression sequence that carries heightened cancer risk. Moreover, other mouse models, like the TxA23 autoimmune gastritis model used here, phenocopy the progression seen in humans . Thus, if IFN‐γ is the key factor mediating the transition to atrophy/metaplasia, it may be critically important for determining which patients with chronic gastritis are at risk for progression to gastric cancer.…”
Section: Discussionmentioning
confidence: 95%
“…Local acid output is crucial for distributing Helicobacter species in the stomach. Moreover, elevated gastric pH can increase susceptibility to certain enteric infection and alter gastric and gut flora . Huang et al showed that long‐term PPI treatment augmented the GC risk in Kunming mice inoculated with MNNG despite their lacking H pylori infection .…”
Section: Environmental Factors Are Associated With Gc Riskmentioning
confidence: 99%
“…Moreover, elevated gastric pH can increase susceptibility to certain enteric infection and alter gastric and gut flora. 87 Huang et al showed that long-term PPI treatment augmented the GC risk in Kunming mice inoculated with MNNG despite their lacking H pylori infection. 88 However, further research is needed to interpret the association between PPI use and GC risk.…”
Section: Proton Pump Inhibitors (Ppis) Are Associated With Increasementioning
confidence: 99%